Adjustment of Optimal Parameters to Control the Temperature in Different Conductors - Amirhossein Oudi; Samaneh Faramarzi; Maryam Hosseini; Yegane Davoodbeygi (مجله مدل سازی در مهندسی)
PID controller is a closed-loop control algorithm and method using the concept of feedback that is used in many industrial processes to control the speed of DC motors, pressure control, temperature control, and so on. For this purpose, a horizontal object with different conductivities was chosen to control its temperature by changing the heat flux. Then, the studied system was written in the state space. In this method, partial differential equations were converted into ordinary differential equations with the help of finite difference, then a suitable controller was designed for temperature control. In this method, the differential equations expressing the process were written as simultaneous first order differential equations. The results show that for the stability of systems with poor thermal conductivity (small α value), should be  K_p/K_i =10. For systems with medium thermal conductivity should be K_p/K_i =0.1. For systems with strong thermal conductivity (large α value) should be K_p/K_i =1. According to the optimization done, Kd was a small value in all three cases, so the PI controller can be used in such systems.